Reinvestigating the Role of IgM in Rabies Virus Postexposure Vaccination - Dorfmeier, Corin L. (American Society for Microbiology, 2013)
B cells secreting IgG antibodies, but not IgM, are thought to be solely responsible for vaccine-induced protection against rabies virus (RABV) infections in postexposure settings. In this report, we reinvestigated the potential for IgM to mediate protection in a mouse model of RABV vaccination. Immunocompetent mice immunized with an experimental live replication-deficient RABV-based vaccine produced virus neutralizing antibodies (VNAs) within 3 days of vaccination. However, mice unable to produce soluble IgM (sIgM(−/−)) did not produce VNAs until 7 days postimmunization. Furthermore, sIgM(−/−) mice were not protected against RABV infection when challenged 3 days postimmunization, while all wild-type mice survived challenge. Consistent with the lack of protection against pathogenic RABV challenge, approximately 50- to 100-fold higher viral loads of challenge virus were detected in the muscle, spinal cord, and brain of immunized sIgM(−/−) mice compared to control mice. In addition, IgG antibody titers in vaccinated wild-type and sIgM(−/−) mice were similar at all time points postimmunization, suggesting that protection against RABV challenge is due to the direct effects of IgM and not the influence of IgM on the development of effective IgG antibody titers. In all, early vaccine-induced IgM can limit dissemination of pathogenic RABV to the central nervous system and mediate protection against pathogenic RABV challenge. Considering the importance for the rapid induction of VNAs to protect against RABV infections in postexposure prophylaxis settings, these findings may help guide the development of a single-dose human rabies vaccine.